TELEVISION ADDICTION AND AUDIENCE: IS IT POSSIBLE NOT TO WATCH TV? - Ali ULUSOY (Fırat University, 2019)
TELEVISION ADDICTION AND AUDIENCE: IS IT POSSIBLE NOT TO WATCH TV? Assist. Prof. Vahit İlhan Erciyes University, Faculty of Communication, Radio, Sinema and Television Department Ali Ulusoy Erciyes University, Faculty of Communication, Journalism Department Abstract Media has always been a matter of debate in daily life and one of the most forthcoming concerns is the excessive time spent hooked at media devices and the quality of this time is criticized. At that point, two things comes to one’s mind, the Internet which is becoming more and more influential and the television which has never lost its impact and importance. Actually, people have so many addictions in daily life at so serious a level as to be defined as illness. Some of these are already notorious physical addictions such as alcohol, drug and cigarette addiction which are also known for their harmful affects. And most of these substance addicts are conscious that their condition is somewhat an illness. However, television addicts are not aware about their situation. It’s highly impossible to tell when the act of TV watching becomes out of control. Specifically, watching more than two hours a day is widely accepted as an important threshold. Dependence on television is an ill defined issue given the multi-variate condition of TV watching with its ever changing nature in daily life praxis. That said, the study focuses on the concepts of television addiction and audience taking television watching as a problem. Firstly, the concept of addiction is analyzed and then some empirical studies on television addiction are comparatively discussed. Daily problems originating from television addition are discussed and some recommendations are developed to get rid of this addiction. Notwithstanding their debated nature, some campaigns and recommendations on the Internet are indicated thus paving the way for awareness on television addiction and opening the issue for argument.